ROOT DISTRIBUTION, NUTRIENT CONCENTRATION AND ACCUMULATION IN ‘GIGANTE’ CACTUS PEAR IRRIGATED WITH SALINE WATER - Fonseca , Varley Andrade (2022)
- In semiarid regions with greater climatic variability, including prolonged droughts and delayed rainy seasons, supplemental irrigation is critical to ensuring yields of forage cactus pear. The objective was to evaluate root distribution and nutrient concentration and accumulation in ‘Gigante’ forage cactus pear subjected to different irrigation regimes. Seven irrigation regimes were tested: no irrigation (rainfed); five liters of medium-salinity water, with an electrical conductivity (EC) of 0.75 dS m-1, applied per linear meter every 15 days; 7% reference evapotranspiration (ETo) with a 15-d irrigation interval (II); 15% ETo with a 7-d II; 33% ETo with a 3-d II; 50% ETo with a 2-d II; and 100% ETo, irrigated daily — high-salinity water, EC of 3.6 dS m-1, was used in the last five treatments. The treatments were laid out in a randomized block design with four replicates. Roots developed best in plants irrigated at 50% ETo with a 7-d II. Applying high-salinity water at 15% ETo with a 7-d irrigation interval promotes higher concentrations of P, Ca, Mg and S in cladodes of cactus pear. Applying high-salinity water at 33% ETo with a 3-d II promotes higher uptake/accumulation of P, Ca, Mg, S and Zn in cladodes of ‘Gigante’ forage cactus pear.